Counselors-in-training evaluation of faculty and site supervisors’ competency and effectiveness - Cain, Amy E. (Kansas State University, 2023)
Because clinical supervision plays a vital role in the education and preparation of counselors-in-training, interest in best practices in supervision and competency-based supervision has increased. The purpose of this quantitative study was to examine how counselors-in-training perceive the competency of faculty and site supervisors and how the type of supervisors and supervisors’ perceived level of experience impacts the counselors-in-trainings’ ratings of supervisory competency. Using convenience sampling, counselors-in-training from CACREP-accredited programs (n = 77) completed an online survey rating supervisors’ competency for a total of 230 faculty and site supervisors. Surveys consisted of demographic information and the instrument, the Supervision Evaluation and Supervisory Competence (SE-SC) short version scale (Gonsalvez, 2020). Overall, the results of this study indicated that the role of being a faculty supervisor or site supervisor did not yield substantial differences in perceived supervisory competency. However, when examining the differences in level of supervisory experience, the results yielded a multitude of differences, notably between novice- and intermediate-level supervisors and novice- and expert-level supervisors. An additional finding revealed a high frequency of inadequate or negative supervision experiences. Implications, limitations, and recommendation for research and practice based off these findings are discussed.
Keywords: Counselor education; Supervision; Counselor-in-training; Supervisors; Supervisee; Competency